The Women's Fight : The Civil War's Battles for Home, Freedom, and Nation - Glymph, Thavolia, 1951- (Book collections on Project MUSE., 2020)
"Historians of the Civil War often speak of "wars within a war"--The military fight, wartime struggles on the home front, and the political and moral battle to preserve the Union and end slavery. In this broadly conceived book, Thavolia Glymph provides a comprehensive new history of women's roles and lives in the Civil War--North and South, white and black, slave and free--showing how women were essentially and fully engaged in all three arenas."--